2007
DOI: 10.1159/000134478
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-Releasing Peptide Receptor Expression in Cervical Cancer

Abstract: Objectives: It was the aim of this study to evaluate whether cervical neoplasms and adjacent tissues express the gastrin-releasing peptide receptor (GRPR) and whether there is a significant difference in its distribution among preinvasive and invasive cancers. Methods: Sections of paraffin-embedded cervical tumors (n = 88) and non-neoplastic control cervical tissues (n = 14) obtained from women registered in the Pathology Department, Academic Hospital, Federal University of Rio Grande do Sul, Porto Alegre, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Expression of TrkB and GRPR in HT-29 and SW620 cells and colorectal tumor samples was analyzed with immunohistochemistry following the general methods described in previous studies [20,21]. The primary antibodies used were a rabbit polyclonal antibody against GRPR (OPA1-15619; Affinity Bioreagents, Golden, Colo., USA), corresponding to the second extracellular loop of human GRPR, and a mouse monoclonal antibody raised against an extracellular domain of the human TrkB receptor (ab51190; Abcam plc, Cambrigde, UK), corresponding to the portion near the site of phosphorylation of tyrosine 515.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of TrkB and GRPR in HT-29 and SW620 cells and colorectal tumor samples was analyzed with immunohistochemistry following the general methods described in previous studies [20,21]. The primary antibodies used were a rabbit polyclonal antibody against GRPR (OPA1-15619; Affinity Bioreagents, Golden, Colo., USA), corresponding to the second extracellular loop of human GRPR, and a mouse monoclonal antibody raised against an extracellular domain of the human TrkB receptor (ab51190; Abcam plc, Cambrigde, UK), corresponding to the portion near the site of phosphorylation of tyrosine 515.…”
Section: Methodsmentioning
confidence: 99%
“…The primary antibody diluted in solution (1:50) was incubated for 12 h at 4°C, followed by application of the complex biotin streptavidin-biotin-peroxidase (LSAB; Dako) and revelation with diaminobenzidine tetrahydrochloride (DAB Kit, Dako). Cell nuclei were lightly counterstained with HE as a control [20,21]. …”
Section: Methodsmentioning
confidence: 99%
“…In an earlier immunohistochemical study, we found aberrant GRPR expression in dysplastic squamous lesions and invasive squamous carcinomas of the cervix, in contrast to low expression in normal epithelia and endocervices. Based on those findings, we postulated that GRPR could be involved in cervical carcinogenesis [13]. These results prompted us to continue investigating GRPR immunosignaling in cervical smears.…”
Section: Discussionmentioning
confidence: 99%
“…For p16 expression, we used a p16-INK4A-specific monoclonal antibody, clone E6H4 (Dako AS, Glostrup, Denmark), primary antibody. The immunohistochemical methods have been described in our previous study [13]. Briefly, after dewaxing, inactivating endogenous peroxidase activity and blocking cross-reactions with normal serum, 4-µm sections were incubated overnight at 4°C with a diluted solution of the primary antibody (1:50).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation